Infective endocarditis-induced complete closure of a ventricular septal defect and complete heart block in a child - UmadeviKaruru; JayRelan; Shyam S Kothari; Saurabh Kumar Gupta; SachinTalwar (Wolters Kluwer Medknow Publications, 2021)
We hereby report rare occurrence of irreversible complete heart block in a child with tricuspid valve infective endocarditis. The tricuspid valve vegetation also caused complete closure of perimembranous ventricular septal defect, which was later discovered during surgery.